Forma jurídica, escravidão e ferrovias no Brasil do século XIX / Legal form, slavery and railways in Brazil of the XIX century - Augusto, Walter Marquezan (Revista Direito e Práxis, 2019)
DOI: 10.1590/2179-8966/2018/33331 Resumo Parte da historiografia recente demonstra que as ferrovias, nas primeiras décadas de suas construções, ou se valeram de mão de obra escrava ou impuseram condições de trabalho tão duras que tornavam trabalhadores livres indiferentes de escravos. Este trabalho investiga qual forma jurídica permitiu essa ocorrência, que fez com que formas tradicionais de manejo e organização do trabalho identificassem novas experiências laborais à escravidão. Palavras-chave: Forma jurídica; Escravidão; Ferrovias. Abstract Part of recent historiography shows that railways in the early decades of their construction either used slave labor or imposed such harsh working conditions that they made free laborers indifferent from slaves. This work aims to investigate which legal form allowed this occurrence, that made traditional forms of work management and organization identify new labor experiences with slavery. Keywords: Legal form; Slavery; Railways.